Results of neoadjuvant therapy followed by esophagectomy for patients with locally advanced thoracic esophageal squamous cell carcinoma - Lin, Dong; Ma, Longfei; Ye, Ting; Pan, Yunjian; Shao, Longlong; Song, Zuodong; Jiang, Shujun; Chen, Haiquan; Xiang, Jiaqing (Journal of Thoracic Disease; Vol 9, No 2 (February 28, 2017): Journal of Thoracic Disease, 2017)
Background: For patients diagnosed with locally advanced esophageal cancer, neoadjuvant therapy followed by surgery is the most common approach. However, randomized trials resulted in inconsistent conclusions. We conducted this retrospective study to evaluate the influence of neoadjuvant therapy on postoperative events and the influence on disease-free survival (DFS) and overall survival (OS). Methods: We retrospectively reviewed all of the patients underwent surgery following neoadjuvant therapy for locally advanced esophageal squamous cell carcinoma (ESCC) during January 1st, 2013 and December 31st, 2015 in Fudan University Shanghai Cancer Center (FUSCC). Prognostic factors for DFS and OS were identified by univariate and multivariate analyses. Results: A total of fifty patients were included. Regarding postoperative morbidities, pneumonia and leakage occurred in 9 (18.0%) and 6 (12.0%) patients, respectively. For the whole patients, the 1-, 2-, 3-year DFS and OS rates were 57.0%, 48.0%, 42.0% and 86.0%, 73.0%, 62.0%, respectively. Lung metastasis and mediastinal node involvement were the most common relapse patterns. Univariate and multivariate analyses confirmed ypTNM stage as an independent prognostic factor for both DFS and OS; while leakage was an independent prognostic factor for DFS. Conclusions: Neoadjuvant therapy did not increase postoperative morbidities but did achieve favorable survival. The ypTNM stage was an independent prognostic factor for both DFS and OS. Long-term survival needs further investigation.